Hypnotic benzodiazepine receptor agonist exposure during pregnancy and the risk of congenital malformations and other adverse pregnancy outcomes: A systematic review and meta‐analysis. (29th May 2022) - Grigoriadis, Sophie; Alibrahim, Aseel; Mansfield, Joanna K.; Sullovey, Amanda; Robinson, Gail Erlick
Abstract: Objective: To determine if there is an association between antenatal hypnotic benzodiazepine receptor agonist exposure and congenital malformations or other adverse pregnancy outcomes in the offspring. Methods: Databases were searched to January 31, 2021. Cohort studies published in English on congenital malformations or other adverse pregnancy outcomes in infants following exposure compared with those unexposed, were summarized and meta‐analyzed where possible. Results: Following screening, 25 studies were assessed for eligibility and seven included in the meta‐analyses. Five studies were pooled for congenital malformations following first trimester exposure and not statistically significant (OR 0.87, 95% CI 0.56–1.36). The five studies that assessed for preterm birth following anytime exposure did pool to a statistically significant effect (OR 1.49, 95% CI 1.19–1.86); study quality, control for other psychotropic drugs and psychiatric diagnosis did not appear to be moderators. There were two missing studies when examining for publication bias in both of the main analyses above but the revised estimates were similar to the original. Low birth weight (LBW) was significant (three studies, any time exposure, OR 1.51, 1.27–1.78) as was small for gestational age (SGA) (three studies with anytime exposure, OR 1.34, 1.22–1.48). There were too few studies to summarize birth weight, gestational age, respiratory difficulties, APGAR score at 5 min and NICU admission. Conclusions: Pregnancy exposure to hypnotics was not associated with a higher risk for congenital malformations but was associated with an increased risk for preterm birth, LBW and SGA compared with those infants who were not exposed. These findings are consistent with the antidepressant and benzodiazepine literature.